Biomass-derived carbon nanosheets coupled with MoO2/Mo2C electrocatalyst for hydrogen evolution reaction. (22nd August 2022) - Chen, Xiaojun; Sun, Jingjing; Guo, Tianyu; Zhao, Ruihua; Liu, Lu; Liu, Bichan; Wang, Yating; Li, Jinping; Du, Jianping
Abstract: Transition metal carbide such as molybdenum carbide has been widely used in electrolytic water for hydrogen production due to its potential catalytic property. The synthesis of molybdenum carbide-based high-efficient catalysts by simple process remains great challenges. Herein, Mo oxide/carbide material with hybrid morphology was synthesized by carbonizing mixture of lotus roots and Mo salt. The as-obtained material consists of MoO2 /Mo2 C (MOMC) anchored on biomass-derived nitrogen-doped carbon (NC) matrix. The results show that as-prepared material displays leaf-like and belt-like nanosheets, and the MOMC/NC catalyst with optimal Mo contents exhibits an excellent activity with a low overpotential of 138 mV to drive 10 mA cm −2 and Tafel slope is 56.7 mV dec −1 in alkaline medium, indicating that as-prepared catalyst will have promising application in the field of catalysis. Graphical abstract: Image 1 Highlights: Ultrasmall MoO2 /Mo2 C NPs were synthesized by carbonizing lotus roots and Mo salt. Biomass-derived carbon consists of leaf-like and belt-like nanosheets. The as-obtained MoO2 /Mo2 C/C exhibited superior electrocatalytic activity and stability for HER. As-synthesized material is a promising noble metal-free electrocatalyst served as HER.